2017
DOI: 10.1017/s0029665117000301
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient profiling for product reformulation: public health impact and benefits for the consumer

Abstract: The food industry holds great potential for driving consumers to adopt healthy food choices as (re)formulation of foods can improve the nutritional quality of these foods. Reformulation has been identified as a cost-effective intervention in addressing non-communicable diseases as it does not require significant alterations of consumer behaviour and dietary habits. Nutrient profiling (NP), the science of categorizing foods based on their nutrient composition, has emerged as an essential tool and is implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 49 publications
0
29
0
2
Order By: Relevance
“…The products that present mostly excess contents of various critical nutrients should be regulated in their offer and their advertising, as some countries have already done, as well as the implementation of frontal labeling, such as in Chile [ 20 ], Ecuador [ 38 ] and France [ 39 ], and thus be able to include dietary guidelines to promote a healthy and balanced diet, allowing the inclusion of prefabricated foods in a healthy and responsible way [ 40 ]. This should include basic studies regarding the consumption of nutrients in the population to identify the existence of a positive impact on the practice of food selection based on its nutritional quality.…”
Section: Discussionmentioning
confidence: 99%
“…The products that present mostly excess contents of various critical nutrients should be regulated in their offer and their advertising, as some countries have already done, as well as the implementation of frontal labeling, such as in Chile [ 20 ], Ecuador [ 38 ] and France [ 39 ], and thus be able to include dietary guidelines to promote a healthy and balanced diet, allowing the inclusion of prefabricated foods in a healthy and responsible way [ 40 ]. This should include basic studies regarding the consumption of nutrients in the population to identify the existence of a positive impact on the practice of food selection based on its nutritional quality.…”
Section: Discussionmentioning
confidence: 99%
“…The HSR has since been shown to align broadly with the Australian dietary guidelines [25,26] and it has been increasingly adopted and showed to have a benefit on consumer understanding about the healthiness of foods, though clear effects on consumer purchases in supermarkets remain to be proved [27,28]. Nutrient profiling (e.g., HSR) may also have the potential to influence the food industry to reformulate their products to healthier ones [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…While many types of FOP nutrition labeling schemes exist to date, few studies, in countries other than Chile, have investigated the potential impact of FOP nutrition labeling initiatives on the reformulation of food and beverage products by industry through observational rather than predicted (modeling) studies; and all are based on positive labeling systems . Regarding the voluntary Health Star Rating (HSR) system FOP nutrition label in New Zealand, Ni Mhurchu et al found that between 2014 and 2016, some products that carried the HSR underwent healthier reformulation compared with similar products without an HSR .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Food and beverage product reformulation is one means to make unhealthy products healthier, thus contributing to wider prevention efforts to help prevent nutrition-related noncommunicable diseases. [9][10][11][12] The main advantage of using government policies to promote food and beverage product reformulation is that it overcomes the different definitions and targets for reformulation policies by each industry actor. Hawkes et al view reformulation as a food-systems response for obesity prevention.…”
mentioning
confidence: 99%
See 1 more Smart Citation